Behavioral cybersecurity : fundamental principles and applications of personality psychology - Patterson, Wayne, 1945-; Winston-Proctor, Cynthia E. (Boca Raton : CRC Press, 2020)
This book discusses the role of human personality in the study of behavioral cybersecurity for non-specialists. Since the introduction and proliferation of the Internet, cybersecurity maintenance issues have grown exponentially. The importance of behavioral cybersecurity has recently been amplified by current events, such as misinformation and cyber-attacks related to election interference in the United States and internationally. More recently, similar issues have occurred in the context of the COVID-19 pandemic. The book presents profiling approaches, offers case studies of major cybersecurity events and provides analysis of password attacks and defenses. Discussing psychological methods used to assess behavioral cybersecurity, alongside risk management, the book also describes game theory and its applications, explores the role of cryptology and steganography in attack and defense scenarios and brings the reader up to date with current research into motivation and attacker/defender personality traits. Written for practitioners in the field, alongside nonspecialists with little prior knowledge of cybersecurity, computer science, or psychology, the book will be of interest to all who need to protect their computing environment from cyber-attacks. The book also provides source materials for courses in this growing area of behavioral cybersecurity.
Originally published: 2019.
1. Recent Events. 2. Behavioral Cybersecurity. 3. Personality Psychology Theory and Methods of Assessment. 4. Hacker Case Study Personality Analysis and Ethical Hacking. 5. Profiling. 6. Access Control. 7. The First Step: Authorization. 8. Origins of Cryptography. 9. Game Theory. 10. The Psychology of Gender. 11. Turing Tests. 12. Modular Arithmetic and Other Computational Methods. 13. Modern Cryptography. 14. Steganography and Relation to Crypto. 15. A Metric to Measure Attacks/Defenses. 16 Behavioral Economics. 17. Fake News. 18. Exercises: "Hack Labs". 19. Conclusions.
OCLC-licensed vendor bibliographic record.
Keywords: Computer security; Computer fraud; Hacking; Social engineering; COMPUTERS / Cryptography